2015
DOI: 10.1093/pasj/psv073
|View full text |Cite
|
Sign up to set email alerts
|

Systematic features of axisymmetric neutrino-driven core-collapse supernova models in multiple progenitors

Abstract: We present an overview of two-dimensional (2D) core-collapse supernova simulations employing neutrino transport scheme by the isotropic diffusion source approximation. We study 101 solar-metallicity, 247 ultra metal-poor, and 30 zero-metal progenitors covering zero-age main sequence mass from 10.8 M ⊙ to 75.0 M ⊙ . Using the 378 progenitors in total, we systematically investigate how the differences in the structures of these multiple progenitors impact the hydrodynamics evolution. By following a long-term evo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 66 publications
10
92
1
Order By: Relevance
“…Hence a careful observational estimate of the true distribution of explosion energies is now required for a quantitative compari son. In line with longtime 2D simulations (Nakamura et al 2015, Bruenn et al 2016, they also find a weak trend for more mas sive progenitors to explode more energeti cally, which appears to be compatible with observations (Poznanski 2013).…”
Section: The Explosion Landscapesupporting
confidence: 82%
See 1 more Smart Citation
“…Hence a careful observational estimate of the true distribution of explosion energies is now required for a quantitative compari son. In line with longtime 2D simulations (Nakamura et al 2015, Bruenn et al 2016, they also find a weak trend for more mas sive progenitors to explode more energeti cally, which appears to be compatible with observations (Poznanski 2013).…”
Section: The Explosion Landscapesupporting
confidence: 82%
“…3D simula tion can make firm predictions only for progenitors at the lowmass end, where Melson et al (2015b) pre dict an explosion energy of ~10 50 erg for a 9.6 M ⊙ pro genitor. Selfconsistent 2D simulations can be taken well beyond the first second (Mül ler 2015, Bruenn et al 2016) and are cheap enough to scan a wide range of progeni tor models (Nakamura 2015), but cannot be trusted to predict the energetics of the explosion correctly (Müller 2015).…”
Section: Multidimensional Modelsmentioning
confidence: 99%
“…Except for the least massive supernova progenitors (Kitaura et al 2006;Müller et al 2012b), successful first-principle simulations of supernova explosions (Buras et al 2006;Marek & Janka 2009;Müller et al 2012aMüller et al ,b, 2013Janka et al 2012;Bruenn et al 2013Bruenn et al , 2016Suwa et al 2010;Nakamura et al 2015;Takiwaki et al 2012Takiwaki et al , 2014Summa et al 2015;O'Connor & Couch 2015) consistently show the persistence of accretion downflows for many hundreds of milliseconds after shock revival -and in many cases to the very end of the simulations so that the final explosion parameters of the models cannot be determined yet. A more quantitative analysis of the mass fluxesṀ out andṀ acc in neutrinodriven outflows and cold accretion downflows in the long-time simulations of Müller (2015) revealed that the accretion through downflows completely outweighs the outflow rate for a long time,…”
Section: Accretion After Shock Revivalmentioning
confidence: 99%
“…This behavior is the reverse of what might be expected if low compactness signaled greater explodability. Finally, the work of Nakamura et al (2015) suggests that though they see a weak correlation, it is not monotonic with compactness. In fact, many of their plots versus compactness resemble scatter plots.…”
Section: Compactnessmentioning
confidence: 99%